Locating the cultural significance of foreign diplomatic representation to the city : the cases of the US Dutch and Brasilian missions in the City of Tshwane - Muhr, Stephan (University of Pretoria, 2016)
Mini Dissertation (MA)--University of Pretoria, 2015.